2014
DOI: 10.1074/jbc.m114.569996
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Cardiac Na+ Channel Nav1.5 by Carbon Monoxide

Abstract: Background: CO poisoning causes cardiac arrhythmias, in part via modulation of the cardiac Na+ channel, Nav1.5.Results: CO inhibition of peak recombinant Nav1.5 current occurs via nitric oxide formation and is also dependent on channel redox state.Conclusion: CO inhibits peak recombinant Nav1.5 current via a mechanism distinct from activation of the late Na+ current.Significance: CO may induce Brugada-like arrhythmias via inhibition of peak Na+ current.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“… 63 Peak inward Na + current inhibition by CO is also NO dependent. 64 Inhibition of the cardiac L-type Ca 2+ current by CO is dependent on mitochondrial ROS production but independent of NO formation. 65 Most recently, we have shown that cardiac ERG (Kv11.1) channels are also inhibited by CO, specifically via the formation of ONOO − .…”
Section: Discussionmentioning
confidence: 99%
“… 63 Peak inward Na + current inhibition by CO is also NO dependent. 64 Inhibition of the cardiac L-type Ca 2+ current by CO is dependent on mitochondrial ROS production but independent of NO formation. 65 Most recently, we have shown that cardiac ERG (Kv11.1) channels are also inhibited by CO, specifically via the formation of ONOO − .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the literature contains several reports of nonheme targets of CO ( 31 ), including examples of nonheme iron(II) carbonyls, including metals coordinated to S from cysteine and/or N from histidine. These ligands may constitute targets in cation channels ( 21 ) or in bacterial ion channels, leading to subsequent respiratory stimulation ( 74 ). Other examples of nonheme interactions include CO binding to iron in [Fe]-, [Fe-Fe]- and [Fe-Ni]-hydrogenases as in Chlamydomonas ( 66 ).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism of this phenomenon is not well understood, but it has been proposed that depends on the increase of the number of Ca 2+ binding sites (Wang et al, 1997 ), expression of the alpha subunit (Wu et al, 2002 ), modulation by NO (Wang and Wu, 2003 ), and a metal-dependent like coordination of CO by Cys at position 911 (C911) (Williams et al, 2008 ; Telezhkin et al, 2011 ). Other ion channels are also affected by CO, such as a 70-pS K + channel in the thick ascending limb of Henle's loop (Liu et al, 1999 ), Kv2.1 (Dallas et al, 2011 ), hTREK-1 (Dallas et al, 2008 ), the amiloride-sensitive Na + channel (Althaus et al, 2009 ), Nav1.5 channels (Elies et al, 2014 ), Cav3.2 (Boycott et al, 2013 ), and P2X2 receptors (Wilkinson et al, 2009 ). In the case of Cav3.2 channels, CO induced-inhibition was dependent on the activation of an extracellular thioredoxin-dependent mechanism (Scragg et al, 2008 ).…”
Section: Carbon Monoxide Modulates Ion Channelsmentioning
confidence: 99%